REFORMULATION OF LEGAL PROTECTION FOR WOMEN’S RIGHTS FOLLOWING DIVORCE: A Normative Study - Nur Faizah (MAQASHID, 2026)
Divorce not only terminates the marital relationship but also generates legal issues concerning the fulfillment of women’s rights, particularly the rights to maintenance, housing, child custody, and economic protection after divorce. Although the legal framework provides various forms of protection for women, its implementation continues to face challenges at both normative and practical levels. This study aims to examine the legal construction of protection for women’s rights after divorce and to formulate a model for reconstructing legal protection that is more responsive to women’s needs and vulnerabilities. This research employs a descriptive-analytical qualitative method with a normative legal approach, combining statutory analysis of the Marriage Law, the Compilation of Islamic Law, Supreme Court Circulars, and Supreme Court Regulations with a review of prior scholarship. The findings indicate that legal protection for women after divorce continues to encounter a gap between normative recognition and the realization of rights in practice, arising from weak enforcement mechanisms, limited access to justice, economic inequality, and insufficient legal literacy among women. In response, this article formulates a model for reconstructing legal protection directed at strengthening enforcement mechanisms—including through cross-agency institutional innovation—simplifying access to justice, and integrating principles of equality and protection for vulnerable groups into family law, so that the protection system moves beyond normative recognition and effectively guarantees the fair and sustainable fulfillment of women’s rights.